2017
DOI: 10.4172/2375-4494.1000366
|View full text |Cite
|
Sign up to set email alerts
|

Association between Family Meals and the Adherence to the Mediterranean Diet in Spanish Adolescents

Abstract: Introduction: Few studies have assessed the role of family meals in the Mediterranean diet (MD). Simultaneously, family meal frequency (FMF) has been associated with healthier lifestyles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
1
0
0
Order By: Relevance
“…Several studies have shown that eating at least one meal per day with a family member has a positive impact on general health and avoiding obesity [33]. As in the present study, studies carried out in Italy and Spain also observed a significant association between MD adherence and eating breakfast with the family [34,35].…”
Section: Discussionsupporting
confidence: 83%
“…Several studies have shown that eating at least one meal per day with a family member has a positive impact on general health and avoiding obesity [33]. As in the present study, studies carried out in Italy and Spain also observed a significant association between MD adherence and eating breakfast with the family [34,35].…”
Section: Discussionsupporting
confidence: 83%